Preparation method and application of coal-based hard carbon negative electrode material

Through the methods of deaze, microarc oxidation and carbonization, a coal-based hard carbon negative electrode material with excellent performance was prepared, which solved the problems of low material performance and complex preparation process in the prior art, and achieved efficient sodium storage capacity and Coulomb efficiency.

CN119750547AActive Publication Date: 2025-04-04HARBIN INST OF TECH

Patent Information

Application Number
CN202510063308.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-15
Publication Date
2025-04-04
Estimated Expiration
2045-01-15

AI Technical Summary

Technical Problem

The existing hard carbon material prepared by coal-based precursors after high temperature treatment has low efficiency and reversible charge and discharge capacity, and the pickling removal operation is complicated, so the use of hydrofluoric acid is dangerous.

Method used

The coal-based hard carbon negative electrode material is prepared by deaze treatment, microarc oxidation treatment and carbonization treatment. The HF gas produced by decomposing the fluorine source during the carbonization process reacts with SiO2 impurities in the coal raw materials, combines the impurity removal and carbonization steps, simplifies the process and introduces the pore structure.

Benefits of technology

The sodium storage capacity, first-time Coulomb efficiency and rate performance of coal-based hard carbon materials is improved, the preparation process is simplified, and the use of dangerous hydrofluoric acid is avoided.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119750547A_ABST
    Figure CN119750547A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a coal-based hard carbon negative electrode material, and belongs to the field of preparation of secondary battery materials. The problems that after an existing coal-based precursor is subjected to high-temperature treatment, the coulombic efficiency and the reversible charge-discharge specific capacity of a prepared hard carbon material are low, acid pickling removal operation is complex, and hydrofluoric acid is dangerous are solved. The preparation method comprises the following steps: 1, deliming treatment; 2, micro-arc oxidation treatment; and 3, carbonizing. According to the application, the material is used for preparing a secondary ion battery negative electrode material. The invention is used for preparation and application of the coal-based hard carbon negative electrode material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of secondary battery material preparation. Background Art

[0002] Renewable energy generation such as solar energy and wind energy is intermittent and unstable. To integrate them into the power grid smoothly and safely requires the development of efficient and stable energy storage technology. Sodium resources are abundant in nature and are cheap. In addition, sodium has a suitable redox potential (compared to Li + / Li high 0.3V), the cost can be significantly reduced by using low-cost sodium-based raw materials and aluminum foil current collectors. In this case, sodium-ion batteries can be used in large-scale energy storage and other fields that focus on cost rather than energy density.

[0003] The negative electrode material stores Na + The electrochemical mechanisms of sodium storage can be divided into the following categories: carbon-based materials, conversion materials, alloying materials and organic materials. Carbon-based materials have low cost and are widely studied, but the specific sodium storage mechanism is still unclear. Conversion / alloying reactions can provide higher theoretical specific capacity based on multi-electron transport, but the material changes greatly in volume during the cycle, has poor rate performance and fast capacity decay. Organic materials have flexible structures and high theoretical specific capacity, but they dissolve in electrolytes and have low conductivity.

[0004] The raw materials of hard carbon precursors are abundant. Currently, the precursor raw materials used for hard carbon mainly include biomass, resin-based and petroleum-based. The hard carbon prepared by resin-based has obvious performance advantages, but the cost is high and industrialization is difficult; petroleum-based precursors are low-cost, the raw materials are easy to obtain, and the cost performance is high, but the performance is average; biomass precursors show higher reversible charge and discharge specific capacity and better cycle performance, but the yield is low. According to the different degrees of metamorphism, coal can be divided into anthracite, bituminous coal, sub-bituminous coal and lignite. Coal-based materials have a higher carbon content and a higher yield.

[0005] In the prior art, after high-temperature treatment of coal-based precursors, the coulombic efficiency and reversible charge-discharge specific capacity of hard carbon materials are low, and the ash in the raw materials is generally removed by acid washing. In particular, silicon-containing impurities are often removed by hydrofluoric acid washing, which is a relatively complicated operation and the hydrofluoric acid used is relatively dangerous. Summary of the invention

[0006] The present invention aims to solve the problems that after the existing coal-based precursor is treated at high temperature, the coulombic efficiency and reversible charge-discharge specific capacity of the hard carbon material prepared are low, the acid washing and removal operation is relatively complicated, and the hydrofluoric acid used is relatively dangerous, and a method for preparing a coal-based hard carbon negative electrode material and its application are provided.

[0007] A method for preparing a coal-based hard carbon negative electrode material is completed by the following steps:

[0008] 1. Deashing treatment:

[0009] The raw coal is ball-milled, sieved and dried to obtain dry coal powder, the dry coal powder is added into a hydrochloric acid aqueous solution for uniform dispersion, then deashed, and finally filtered, washed with water and vacuum dried to obtain deashed coal powder;

[0010] 2. Micro-arc oxidation treatment:

[0011] The deashed coal powder is subjected to micro-arc oxidation treatment to obtain an oxidation precursor;

[0012] 3. Carbonization:

[0013] The oxidation precursor and the fluorine source powder are evenly mixed to obtain a mixed powder, and then the mixed powder is carbonized to obtain a coal-based hard carbon negative electrode material, thereby completing the preparation method of the coal-based hard carbon negative electrode material.

[0014] The invention discloses an application of a coal-based hard carbon negative electrode material, which is used for preparing a negative electrode material for a secondary ion battery.

[0015] The beneficial effects of the present invention are:

[0016] (1) The present invention utilizes the HF gas generated by the decomposition of the fluorine source during the carbonization process to react with the SiO2 impurity in the coal raw material, thereby combining the impurity removal step and the carbonization step into one, simplifying the preparation process and avoiding the use of hydrofluoric acid.

[0017] (2) More oxygen-containing functional groups are introduced into the precursor by micro-arc oxidation to promote the cross-linking reaction between molecules during the carbonization process and produce more porous structures.

[0018] (3) The HF gas produced by the decomposition of the fluorine source at high temperature reacts with the SiO2 impurities in the coal raw material, introducing some pores in the process of removing impurities, further improving the performance of the material.

[0019] (4) The present invention introduces a porous structure into coal during carbonization by in-situ impurity removal and pore formation and in-situ cross-linking. The coal-based hard carbon material prepared according to the method of the present invention is used as a negative electrode material for sodium ion batteries and has high sodium storage capacity, first coulomb efficiency, and rate performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 This is a SEM image of the coal-based hard carbon negative electrode material prepared in Example 2;

[0021] Figure 2 X-ray diffraction patterns of coal-based hard carbon negative electrode materials prepared in Example 2 and Comparative Example 1;

[0022] Figure 3The charge and discharge curves of the sodium ion battery prepared using the coal-based hard carbon negative electrode materials of Example 2 and Comparative Example 1;

[0023] Figure 4 This is a graph showing the cycle performance of sodium ion batteries prepared using the coal-based hard carbon negative electrode materials of Example 2 and Comparative Example 1. DETAILED DESCRIPTION

[0024] Specific implementation method 1: This implementation method is a method for preparing a coal-based hard carbon negative electrode material, which is completed by the following steps:

[0025] 1. Deashing treatment:

[0026] The raw coal is ball-milled, sieved and dried to obtain dry coal powder, the dry coal powder is added into a hydrochloric acid aqueous solution for uniform dispersion, then deashed, and finally filtered, washed with water and vacuum dried to obtain deashed coal powder;

[0027] 2. Micro-arc oxidation treatment:

[0028] The deashed coal powder is subjected to micro-arc oxidation treatment to obtain an oxidation precursor;

[0029] 3. Carbonization:

[0030] The oxidation precursor and the fluorine source powder are evenly mixed to obtain a mixed powder, and then the mixed powder is carbonized to obtain a coal-based hard carbon negative electrode material, thereby completing the preparation method of the coal-based hard carbon negative electrode material.

[0031] The beneficial effects of this embodiment are:

[0032] (1) This embodiment utilizes the HF gas generated by the decomposition of the fluorine source during the carbonization process to react with the SiO2 impurity in the coal raw material, thereby combining the impurity removal step and the carbonization step into one, simplifying the preparation process and avoiding the use of hydrofluoric acid.

[0033] (2) More oxygen-containing functional groups are introduced into the precursor by micro-arc oxidation to promote the cross-linking reaction between molecules during the carbonization process and produce more porous structures.

[0034] (3) The HF gas produced by the decomposition of the fluorine source at high temperature reacts with the SiO2 impurities in the coal raw material, introducing some pores in the process of removing impurities, further improving the performance of the material.

[0035] (4) This embodiment introduces a porous structure into the coal during carbonization by means of in-situ impurity removal and pore formation and in-situ cross-linking. The coal-based hard carbon material prepared according to the method of the present invention is used as a negative electrode material for sodium ion batteries, and has high sodium storage capacity, first coulomb efficiency, and rate performance.

[0036] Specific implementation method 2: This implementation method is different from specific implementation method 1 in that the raw coal in step 1 is one or a combination of bituminous coal, sub-bituminous coal and lignite. The rest is the same as specific implementation method 1.

[0037] Specific implementation method 3: This implementation method is different from specific implementation method 1 or 2 in that: the ball milling in step 1 is performed at a rotation speed of 300 rpm to 400 rpm for 2 h to 5 h; the sieving in step 1 is performed through a 100 mesh sieve. The rest is the same as specific implementation method 1 or 2.

[0038] Specific embodiment 4: This embodiment differs from specific embodiments 1 to 3 in that: the concentration of the hydrochloric acid aqueous solution in step 1 is 3 mol / L to 5 mol / L; the volume ratio of the mass of the dry coal powder in step 1 to the hydrochloric acid aqueous solution is 1 g: (10 to 30) mL. Others are the same as specific embodiments 1 to 3.

[0039] Specific embodiment 5: This embodiment is different from specific embodiments 1 to 4 in that the deashing treatment in step 1 is carried out at a temperature of 25°C to 40°C and a rotation speed of 500rpm to 700rpm for 10h to 15h. The rest is the same as specific embodiments 1 to 5.

[0040] Specific embodiment 6: This embodiment is different from specific embodiments 1 to 5 in that the vacuum drying described in step 1 is carried out at a temperature of 70° C. to 90° C. for 20 h to 24 h. The rest is the same as specific embodiments 1 to 5.

[0041] Specific embodiment 7: This embodiment is different from specific embodiments 1 to 6 in that the micro-arc oxidation treatment described in step 2 is specifically carried out at a power of 30 kW to 60 kW, a frequency of 800 Hz to 1200 Hz, a duty cycle of 30% to 50% and a current density of 8 A / dm 2 ~12A / dm 2 Under the condition of , the deashed coal powder is subjected to micro-arc oxidation treatment for 20min to 50min. The rest is the same as the specific embodiments 1 to 6.

[0042] Specific embodiment 8: This embodiment differs from specific embodiments 1 to 7 in that the fluorine source powder in step 3 is an organic fluorine source and an inorganic fluorine source or a mixture of both; the chemical formula of the organic fluorine source is (C a H b F c ) n , wherein a=1-4, b=0-6, c=1-6, n=1-10000; the chemical formula of the inorganic fluorine source is MFm , wherein M = Fe, Zn, Na, Li, NH4, Cr, Sb, Ti, Sn or V, m = 1 to 4; the mass percentage of the oxidized precursor in the mixed powder described in step 3 is 70% to 95%. The rest is the same as the specific embodiments 1 to 7.

[0043] Specific embodiment 9: This embodiment differs from specific embodiments 1 to 8 in that: the carbonization treatment described in step 3 is specifically carried out under an inert atmosphere at a heating rate of 1°C / min to 10°C / min, and the temperature is raised to 1000°C to 1400°C, and then the carbonization treatment is carried out under the conditions of an inert atmosphere and a temperature of 1000°C to 1400°C for 2h to 5h; the inert atmosphere is argon or nitrogen. The rest is the same as specific embodiments 1 to 8.

[0044] Specific implementation method ten: This implementation method is an application of a coal-based hard carbon negative electrode material, which is used to prepare a negative electrode material for a secondary ion battery.

[0045] The following examples are used to verify the beneficial effects of the present invention:

[0046] Embodiment 1:

[0047] A method for preparing a coal-based hard carbon negative electrode material is completed by the following steps:

[0048] 1. Deashing treatment:

[0049] The raw coal was ball-milled for 3 hours at a rotation speed of 400 rpm, then passed through a 100-mesh screen and dried to obtain dry coal powder. The dry coal powder was added into a hydrochloric acid aqueous solution and dispersed evenly. Then, the raw coal powder was deashed for 12 hours at a temperature of 30°C and a rotation speed of 600 rpm. After deashing, the raw coal was filtered and washed with water. Finally, the raw coal powder was vacuum-dried for 24 hours at a temperature of 80°C to obtain deashed coal powder.

[0050] The concentration of the hydrochloric acid aqueous solution is 3 mol / L; the volume ratio of the mass of the dry coal powder to the hydrochloric acid aqueous solution is 1 g:20 mL;

[0051] 2. Micro-arc oxidation treatment:

[0052] At a power of 60kW, a frequency of 1000Hz, a duty cycle of 40%, and a current density of 10A / dm 2 Under the condition of , the deashed coal powder was subjected to micro-arc oxidation for 30 min to obtain an oxidized precursor;

[0053] 3. Carbonization:

[0054] The oxidation precursor and the fluorine source powder are evenly mixed to obtain a mixed powder. Under an argon atmosphere, the mixed powder is heated to 1200°C at a heating rate of 5°C / min. Then, the mixed powder is carbonized for 2 hours under an argon atmosphere and a temperature of 1200°C to obtain a coal-based hard carbon negative electrode material.

[0055] The raw coal described in step one is lignite; the lignite is lignite from the Zhalainuoer mining area, in which the mass percentage of ash is 7.64%, the mass percentage of moisture is 10.01%, the mass percentage of volatile matter is 35.72%, and the mass percentage of fixed carbon is 46.63%.

[0056] The fluorine source powder described in step three is an organic fluorine source; the organic fluorine source is polytetrafluoroethylene; the mass percentage of the oxidative precursor in the mixed powder described in step three is 95%.

[0057] Example 2: This example is different from Example 1 in that the mass percentage of the oxidation precursor in the mixed powder in step 3 is 85%. Other aspects are the same as Example 1.

[0058] Example 3: This example is different from Example 1 in that the mass percentage of the oxidation precursor in the mixed powder in step 3 is 70%. Other aspects are the same as Example 1.

[0059] Example 4: This example is different from Example 1 in that the heating rate in step 3 is 1°C / min. The rest is the same as Example 1.

[0060] Example 5: This example is different from Example 1 in that the heating rate in step 3 is 10°C / min. The rest is the same as Example 1.

[0061] Example 6: This example is different from Example 1 in that the carbonization temperature in step 3 is 1000° C. The rest is the same as Example 1.

[0062] Embodiment 7: This embodiment is different from Embodiment 1 in that the carbonization temperature in step 3 is 1400° C. The rest is the same as Embodiment 1.

[0063] Example 8: This example is different from Example 1 in that: the fluorine source powder in step 3 is a mixture of an organic fluorine source and an inorganic fluorine source in a mass ratio of 100:50; the organic fluorine source is polytetrafluoroethylene; and the inorganic fluorine source is ammonium fluoride. The rest is the same as Example 1.

[0064] Example 9: This example is different from Example 1 in that: the fluorine source powder in step 3 is a mixture of an organic fluorine source and an inorganic fluorine source in a mass ratio of 100:100; the organic fluorine source is polytetrafluoroethylene; and the inorganic fluorine source is ammonium fluoride. The rest is the same as Example 1.

[0065] Embodiment 10: This embodiment is different from Embodiment 1 in that: the raw coal described in step 1 is bituminous coal; the bituminous coal is bituminous coal from the Hongshaquan mining area in Xinjiang, wherein the mass percentage of ash is 5%, the mass percentage of water is 7%, the mass percentage of volatile matter is 8%, and the mass percentage of fixed carbon is 80%; the fluorine source powder described in step 3 is a mixture of an organic fluorine source and an inorganic fluorine source in a mass ratio of 100:100; the organic fluorine source is polytetrafluoroethylene; and the inorganic fluorine source is ammonium fluoride. The rest is the same as Embodiment 1.

[0066] Example 11: This example is different from Example 1 in that: the raw coal described in step 1 is sub-bituminous coal; the sub-bituminous coal is sub-bituminous coal from the Hongshaquan mining area in Xinjiang, wherein the mass percentage of ash is 6%, the mass percentage of water is 9%, the mass percentage of volatile matter is 22%, and the mass percentage of fixed carbon is 63%; the fluorine source powder described in step 3 is a mixture of an organic fluorine source and an inorganic fluorine source in a mass ratio of 100:100; the organic fluorine source is polytetrafluoroethylene; and the inorganic fluorine source is ammonium fluoride. The rest is the same as Example 1.

[0067] Example 12: This example is different from Example 1 in that: in step 1, the raw coal is ball-milled for 3 hours at a rotation speed of 300 rpm; the raw coal described in step 1 is sub-bituminous coal; the sub-bituminous coal is sub-bituminous coal from the Hongshaquan mining area in Xinjiang, wherein the mass percentage of ash is 6%, the mass percentage of water is 9%, the mass percentage of volatile matter is 22%, and the mass percentage of fixed carbon is 63%; the fluorine source powder described in step 3 is a mixture of an organic fluorine source and an inorganic fluorine source in a mass ratio of 100:100; the organic fluorine source is polytetrafluoroethylene; the inorganic fluorine source is ammonium fluoride. The rest is the same as Example 1.

[0068] Example 13: This example is different from Example 1 in that: in step 1, the raw coal is ball-milled for 5 hours at a rotation speed of 400 rpm; the raw coal described in step 1 is sub-bituminous coal; the sub-bituminous coal is sub-bituminous coal from the Hongshaquan mining area in Xinjiang, wherein the mass percentage of ash is 6%, the mass percentage of water is 9%, the mass percentage of volatile matter is 22%, and the mass percentage of fixed carbon is 63%; the fluorine source powder described in step 3 is a mixture of an organic fluorine source and an inorganic fluorine source in a mass ratio of 100:100; the organic fluorine source is polytetrafluoroethylene; the inorganic fluorine source is ammonium fluoride. The rest is the same as Example 1.

[0069] Example 14: This example is different from Example 1 in that: in step 3, carbonization is performed under a nitrogen atmosphere; the fluorine source powder in step 3 is a mixture of an organic fluorine source and an inorganic fluorine source in a mass ratio of 100:100; the organic fluorine source is polytetrafluoroethylene; and the inorganic fluorine source is ammonium fluoride. The rest is the same as in Example 1.

[0070] Comparative Example 1: This embodiment is different from Embodiment 1 in that: Step 2 is omitted; and the fluorine source powder is omitted in Step 3. Other aspects are the same as Embodiment 1.

[0071] Performance Test:

[0072] (1) SEM test:

[0073] The coal-based hard carbon negative electrode material prepared in Example 2 was subjected to SEM testing, and the results were as follows: Figure 1 shown. Figure 1 This is a SEM image of the coal-based hard carbon negative electrode material prepared in Example 2; as can be seen from the image, the material has a granular structure with a particle size between 3 and 5 μm.

[0074] (2) X-ray test:

[0075] Figure 2 X-ray diffraction patterns of coal-based hard carbon negative electrode materials prepared in Example 2 and Comparative Example 1; it can be seen from the figure that silicon-containing impurities are removed after co-carbonization with polytetrafluoroethylene.

[0076] (3) Button battery test:

[0077] The coal-based hard carbon negative electrode materials prepared in Examples 1 to 14 and Comparative Example 1 were assembled into button batteries according to the following method:

[0078] The coal-based hard carbon negative electrode materials prepared in Examples 1 to 14 and Comparative Example 1 were used as negative electrodes and assembled into button batteries with sodium sheets, electrolytes and diaphragms in a glove box with oxygen and water contents below 0.1 ppm. The diaphragm was a glass fiber diaphragm Whatman GF / D; the electrolyte was a NaPF6 solution with a NaPF6 concentration of 1 mol / L in the electrolyte, and the solvent was diethylene glycol dimethyl ether (DIGLYME).

[0079] The button cells were tested for their performance using a Xinwei tester. The test conditions were: at a current density of 30 mA g -1 The charge and discharge conditions were as follows: the voltage range was 0-2V, and the cycle was stopped after 3 cycles. At the same time, the rate performance (300mA·g -1 ), the test results are shown in Table 1. Figure 3 The charge and discharge curves of the sodium ion battery prepared using the coal-based hard carbon negative electrode materials of Example 2 and Comparative Example 1 are shown. Figure 4This is a cycle performance diagram of a sodium ion battery prepared using the coal-based hard carbon negative electrode materials of Example 2 and Comparative Example 1; it can be found that the capacity retention rate is increased from 84.1% to 96.9%.

[0080] Table 1

[0081]

[0082] It can be seen from Table 1 that the discharge capacity and rate performance of the button cells made using the coal-based hard carbon negative electrode materials of Examples 1 to 14 are higher than those of Comparative Example 1. The experimental results show that the pores introduced into the example materials can increase the sodium storage capacity of the materials, and the closed-pore structure can improve the first coulombic efficiency.

Claims

1. A method for preparing a coal-based hard carbon negative electrode material, characterized in that It is done in the following steps:

1. Deashing treatment: The raw coal is ball-milled, sieved and dried to obtain dry coal powder, the dry coal powder is added into a hydrochloric acid aqueous solution for uniform dispersion, then deashed, and finally filtered, washed with water and vacuum dried to obtain deashed coal powder; 2. Micro-arc oxidation treatment: The deashed coal powder is subjected to micro-arc oxidation treatment to obtain an oxidation precursor; 3. Carbonization: The oxidation precursor and the fluorine source powder are evenly mixed to obtain a mixed powder, and then the mixed powder is carbonized to obtain a coal-based hard carbon negative electrode material, thereby completing the preparation method of the coal-based hard carbon negative electrode material.

2. The method for preparing a coal-based hard carbon negative electrode material according to claim 1, characterized in that The raw coal described in step 1 is one or a combination of bituminous coal, sub-bituminous coal and lignite.

3. The method for preparing a coal-based hard carbon negative electrode material according to claim 1, characterized in that The ball milling described in step 1 is specifically carried out at a rotation speed of 300 rpm to 400 rpm for 2 h to 5 h; the screening described in step 1 is carried out through a 100-mesh sieve.

4. The method for preparing a coal-based hard carbon negative electrode material according to claim 1, characterized in that The concentration of the hydrochloric acid aqueous solution described in step one is 3 mol / L to 5 mol / L; the volume ratio of the mass of the dry coal powder described in step one to the hydrochloric acid aqueous solution is 1 g: (10 to 30) mL.

5. The method for preparing a coal-based hard carbon negative electrode material according to claim 1, characterized in that The deashing treatment in step 1 is specifically carried out at a temperature of 25° C. to 40° C. and a rotation speed of 500 rpm to 700 rpm for 10 h to 15 h.

6. The method for preparing a coal-based hard carbon negative electrode material according to claim 1, characterized in that The vacuum drying described in step 1 is specifically performed at a temperature of 70° C. to 90° C. for 20 h to 24 h.

7. The method for preparing a coal-based hard carbon negative electrode material according to claim 1, characterized in that The micro-arc oxidation treatment described in step 2 is specifically carried out at a power of 30 kW to 60 kW, a frequency of 800 Hz to 1200 Hz, a duty cycle of 30% to 50% and a current density of 8 A / dm 2 ~12A / dm 2 Under the conditions of , the deashed pulverized coal is subjected to micro-arc oxidation treatment for 20min to 50min.

8. The method for preparing a coal-based hard carbon negative electrode material according to claim 1, characterized in that The fluorine source powder in step 3 is one or a mixture of an organic fluorine source and an inorganic fluorine source; the chemical formula of the organic fluorine source is (C a H b F c ) n , wherein a=1-4, b=0-6, c=1-6, n=1-10000; the chemical formula of the inorganic fluorine source is MF m , wherein M = Fe, Zn, Na, Li, NH4, Cr, Sb, Ti, Sn or V, and m = 1 to 4; the mass percentage of the oxidative precursor in the mixed powder described in step 3 is 70% to 95%.

9. The method for preparing a coal-based hard carbon negative electrode material according to claim 1, characterized in that The carbonization treatment described in step three is specifically to heat the temperature to 1000°C to 1400°C under an inert atmosphere at a heating rate of 1°C / min to 10°C / min, and then carbonize the mixture under the inert atmosphere and at a temperature of 1000°C to 1400°C for 2h to 5h; the inert atmosphere is argon or nitrogen.

10. Use of a coal-based hard carbon negative electrode material prepared as claimed in claim 1, characterized in that It is used to prepare negative electrode materials for secondary ion batteries.

Citation Information

Patent Citations

  • Method of adopting environment-friendly nickel-containing electrolyte to prepare microarc oxidation film layer on surface of magnesium alloy

    CN103726093A

  • Preparation method of low-rank coal-based hard carbon material prepared by blending and co-thermal conversion of waste plastics

    CN114853003A

  • Manufacturing methods of negative current collector, negative plate and lithium battery

    CN117117201A

  • Coal-based derived hard carbon material with novel core-shell carbon framework as well as preparation method and application of coal-based derived hard carbon material

    CN118412450A

  • Pre-Equilibrium System and Method Using Solid-State Devices as Energy Converters Using Nano-Engineered Porous Network Materials

    US20160111564A1

Cited By

  • Preparation method and application of coal-based hard carbon negative electrode material based on low-temperature melting guidance

    CN121516848A